2020
DOI: 10.1177/1178638820905992
|View full text |Cite
|
Sign up to set email alerts
|

Meeting Calorie and Protein Needs in the Critical Care Unit: A Prospective Observational Pilot Study

Abstract: Background: Inadequate calorie and protein intake during critical illness is associated with poor clinical outcomes. Unfortunately, most critically ill patients do not consume adequate levels of these nutrients. An enteral formula with appropriate macronutrient composition may assist patients in meeting nutritional goals. Design: This study was a single center, prospective, observational study of 29 adults in the medical intensive care unit who required enteral nutrition for at least 3 days. Subjects received … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Adequate calorie and protein intake is important for recovery in critically ill patients [ 33 , 34 ]. Adequate nutritional support may also be important in neurocritically ill patients.…”
Section: Discussionmentioning
confidence: 99%
“…Adequate calorie and protein intake is important for recovery in critically ill patients [ 33 , 34 ]. Adequate nutritional support may also be important in neurocritically ill patients.…”
Section: Discussionmentioning
confidence: 99%
“…In this aspect, a nutritive support is an important constituent of the therapy. Besides, enteral nutrition helps maintain structural [ 42 ] and functional condition of the intestine including activation of T-cell association of lymphoid tissue [ 43 ] and activation of neutrophils [ 44 ]. Enteral nutrition allows for preservation of the mucous barrier which prevents translocation of bacteria from the intestinal lumen to the bloodstream and thereby hinders infection from spreading [ 45 ].…”
Section: Nutritional Disorders and Nutritive Support In Chronic Criti...mentioning
confidence: 99%
“…Caloric value should be increased up to 100% by day 7 [ 46 ]. It has been established [ 47 , 48 ] that the increase of calories in the nutrition >70% during the first 12–24 h after the admission to ICRU does not lead to the reduction of hospital stay and better survival.…”
Section: Nutritional Disorders and Nutritive Support In Chronic Criti...mentioning
confidence: 99%
“…Optimizing critical patient nutrition improves clinical outcomes [12][13][14] . This is consistent with our experimental results, which showed that reducing caloric and protein de cits is associated with successful ventilator weaning and signi cantly lower mortality (Fig.…”
Section: Secondary Outcomes and Clinical Bene Tsmentioning
confidence: 99%